Integrative analysis of the expression profiles of whole coding and non-coding RNA transcriptomes and construction of the competing endogenous RNA networks for chronic obstructive pulmonary disease - Feng, Xueyan; Dong, Hui; Li, Beibei; Yu, Liang; Zhu, Jinyuan; Lou, Caili; Zhang, Jin (Frontiers in Genetics, 2023)
Background: The pathogenesis of Chronic Obstructive Pulmonary Disease (COPD) is implicated in airway inflammation, oxidative stress, protease/anti-protease and emphysema. Abnormally expressed non-coding RNAs (ncRNAs) play a vital role in regulation of COPD occurrence and progression. The regulatory mechanisms of the circRNA/lncRNA-miRNA-mRNA (competing endogenous RNA, ceRNA) networks might facilitate our cognition of RNA interactions in COPD. This study aimed to identified novel RNA transcripts and constructed the potential ceRNA networks of COPD patients. Methods: Total transcriptome sequencing of the tissues from patients with COPD (COPD) (n=7) and non-COPD control subjects (Normal) (n=6) was performed, and the expression profiles of differentially expressed genes (DEGs), including mRNAs, lncRNAs, circRNAs, and miRNAs, were analyzed. The ceRNA network was established based on the miRcode and miRanda databases. Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Ontology (GO), Gene Set Enrichment Analysis (GSEA), and Gene set variation analysis (GSVA) were implemented for functional enrichment analysis of DEGs. Finally, CIBERSORTx was extracted to analyze the relevance between hub genes and various immune cells. The Starbase and JASPAR databases were used to construct hub-RNA binding proteins (RBPs) and lncRNA-transcription factor (TF) interaction networks. Results: A total of 1,796 mRNAs, 2,207 lncRNAs, and 11 miRNAs showed differentially expression between the lung tissue samples from the normal and COPD groups. Based on these DEGs, lncRNA/circRNA-miRNA-mRNA ceRNA networks were constructed respectively. In addition, ten hub genes were identified. Among them, RPS11, RPL32, RPL5, and RPL27A were associated with the proliferation, differentiation, and apoptosis of the lung tissue. The biological function revealed that TNF-α via NF-κB and IL6/JAK/STAT3 signaling pathways were involved in COPD. Conclusions: Our research constructed the lncRNA/circRNA-miRNA-mRNA ceRNA networks, filtrated ten hub genes may regulate the TNF-α/NF-κB, IL6/JAK/STAT3 signally pathways, which indirectly elucidated the post-transcriptional regulation mechanism of COPD and lay the foundation for excavating the novel targets of diagnosis and treatment in COPD.